Critical Realism and Econometrics - Ida Wolden Bache (Norges Bank, 2003)
In "Economics and Reality" (1997) Tony Lawson advocates a perspective on social reality labelled critical realism. Critical realism maintains that strict regularities between observable events are the exception rather than the rule in the social world. This is a negative argument for econometrics which is seen to rely on the identification of such regularities. By contrast, the notion of explanation sustained by critical realism does not depend on an abundance of strict event regularities. In this essay we examine whether econometrics is indeed incompatible with critical realism. This involves asking the following questions: Is Tony Lawson's characterization of econometrics accurate? In what sense, if any, could econometrics be useful for critical realist researchers? The discussion of econometrics is confined to the so-called LSE approach to econometric modelling of macroeconomic time series.
hdl:11250/2498623
Keywords: B41; C50; 330; critical realism; econometric methodology